Subjective Happiness in Slovakia: Reliability and Validity of Measuring Happiness through the Subjective Happiness Scale - Babinčák, Peter (European Journal of Mental Health, 2018)
The objective of the present research was to assess the possibilities of measuring happiness in Slovakia and verify psychometric properties of the Slovak version of the Subjective Happiness Scale (SHS; LYUBOMIRSKY & LEPPER 1999). Based on a systematic comparison of features of 16 language versions of SHS, satisfactory and interculturally comparable characteristics have been found of the scale, which still does not have a version adapted for the Slovak language environment. Data were collected from 977 respondents (three community samples and four samples of university students) aged 13–75 years. With the use of EFA and CFA, a single-factor structure of SHS was confirmed. SHS showed adequate internal consistency value (α = 0.773) and test-retest reliability (r = 0.615). Convergent validity was verified a) by comparing with another instrument to measure subjective happiness; b) by correlations with subjective well-being and quality of life; c) by correlations with other variables: personality traits, self-esteem, optimism, depression, religiosity, spirituality, family functions, compliance with and internalisation of norms. No significant differences in SHS values on the basis of gender, religion, and education were detected. It can be concluded that the short four-item scale which was used has satisfactory psychometric properties and offers opportunities for the rapid assessment of subjective happiness.